Andragogy Approach in the Utilization of Liquid Smoke Coconut Waste as a Vegetable Insecticide for Coconut Farming Community - Wahyu Ana Pria Utama (Jurnal Serambi Ilmu, 2022)
Appropriate technology learning must be able to touch all levels of society.In this research, we combine formal education with informal education inthe form of participatory education for adults. Participatory education isintended to involve the community directly participating in theimplementation of this research by seeing, doing, and observing the process.The aim is how to utilize liquid smoke from coconut frond waste as avegetable insecticide as well as a repellent or insect repellent because itcontains phenol or phenolic, antioxidant, antimicrobial in coconut plants inthe people of Aceh Besar. Based on the results of chemical analysis in liquidsmoke found elements or chemical substances, such as acetic acid, carboxyland phenol. This study aims to determine how the effect of temperature andduration of combustion on the yield (final product), such as the degree ofacidity, acetic acid content, and phenol content. This research was carriedout using a factorial Completely Randomized Design (CRD) with two mainfactors, namely: Factor-1 burning for 2-3 hours and Factor-2 with variationsin temperature 200oC, 250oC, 300oC, 350oC, 400oC. The best result forliquid smoke is 25% (w/w) of 20 kg of dry matter from coconut fronds. Theaverage content of acetic acid (CH3COOH) is 6.45 mg/ml. And the contentof phenol (C6H6O) is 3.76 ppm.